Perceived justice in service Recovery and customer satisfaction: Evidence from the Malaysian Hotel Industry - Cheng, Boon Liat * (Publisher, 2015)
The tense competition in service industry has driven companies to place extra attention towards service recovery to ensure continuous success. Due to the astonishing rate of the development of the hotel industry in Malaysia for the past decade, it has urged hotel providers to reconsider their business strategy in order to achieve customer satisfaction and sustain their business. As such, the purpose of this study is to examine the effects of service recovery dimensions (distributive justice, procedural justice and interactional justice) on customer satisfaction, particularly in the context of hotel industry in Malaysia. Data collection was done through self-administered questionnaires distributed to 400 respondents who have experienced staying in any Malaysian hotels. To ensure the reliability and validity of the data set, various statistical tests were performed such as preliminary and descriptive analysis and reliability test. Regression analysis was performed to examine hypothesised relationships. The findings revealed that the respective service recovery dimensions are significantly related to customer satisfaction. In summary, a better understanding of service recovery aids hotel providers in handling service failures more effectively otherwise it might result in customer dissatisfaction with poor service recovery strategy.